Pogostemon nudus sp. nov. (Lamiaceae) from Thailand. (26th April 2017) - Bongcheewin, Bhanubong; Pramali, Kanjana; Traiperm, Paweena; Chantaranothai, Pranom; Paton, Alan
Abstract : A new species of Pogostemon Desf., P. nudus Bongcheewin & Pramali, is described, illustrated and compared with the similar P. menthoides from Thailand. Morphological characters, especially the micromorphology of nutlets and leaf epidermis, and conservation status in accordance with the IUCN red list categories and criteria are described and discussed. In addition, a key to all species of P . sect. Pogostemon known from Thailand is presented.